Assessing ship collision risks in maritime transport based on seafarers’ experience - Quoc Hai, Dang; Gia Huy, Dinh; Anh Kha, Tran (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2024)
Assessing ship collision risks considering human factors presents persistent challenges due to the multivariate uncertainties faced by seafarers. Therefore, this study proposes a fuzzy-logic-based method to model ship collision risks in an area considering human factors. This method utilizes a hierarchical fuzzy system consisting of two fuzzy systems, fuzzy system 1 and fuzzy system 2, which are used to calculate the temporary risks and human factors, respectively. Aggregating the risks from both subsystems produces the overall collision risk index. This approach streamlines on-board risk appraisal, thereby reducing the navigator workload. While the current study delineates the risk modeling methodology, succeeding works validate the framework through simulated experiments. With adequate verification, this hierarchical fuzzy approach can assist next-generation risk-regulated navigation practices and enrich maritime agencies' traffic risk management.